Recent Trends in Mechatronics Towards Industry 4.0 : Selected Articles from iM3F 2020, Malaysia - Innovative Manufacturing, Mechatronics and Materials Forum 645510; Ahmad Fakhri Ab. Nasir, editor 645348; Ahmad Najmuddin Ibrahim, editor 645512; Ismayuzri Ishak, editor 645513; Nafrizuan Mat Yahya, editor 645514; Muhammad Aizzat Zakaria, editor 524299; Anwar P. P. Abdul Majeed, editor 645313; SpringerLink (Online service) (Singapore : Springer, 2022)
This book presents part of the iM3F 2020 proceedings from the Mechatronics track. It highlights key challenges and recent trends in mechatronics engineering and technology that are non-trivial in the age of Industry 4.0. It discusses traditional as well as modern solutions that are employed in the multitude spectra of mechatronics-based applications. The readers are expected to gain an insightful view on the current trends, issues, mitigating factors as well as solutions from this book.